2010
DOI: 10.1007/s11104-010-0635-4
|View full text |Cite
|
Sign up to set email alerts
|

Dual benefit from a belowground symbiosis: nitrogen fixing rhizobia promote growth and defense against a specialist herbivore in a cyanogenic plant

Abstract: Legume-associated nitrogen-fixing bacteria play a key role for plant performance and productivity in natural and agricultural ecosystems. Although this plant-microbe mutualism has been known for decades, studies on effects of rhizobia colonisation on legume-herbivore interactions are scarce. We hypothesized that additional nitrogen provided by rhizobia may increase plant resistance by nitrogen-based defense mechanisms. We studied this below-aboveground interaction using a system consisting of lima bean (Phaseo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 50 publications
2
68
0
3
Order By: Relevance
“…However, this is not necessarily the case, as rhizobia have been shown to also affect plant defense responses directly (e.g., Thamer et al, 2011) and indirectly (Godschalx et al, 2015). The latter is illustrated by a study with potted plants placed in the field that reported positive effects of the addition of Rhizobium sp.…”
Section: The Effect Of Nitrogen-fixing Rhizobia On Aboveground Herbivmentioning
confidence: 99%
“…However, this is not necessarily the case, as rhizobia have been shown to also affect plant defense responses directly (e.g., Thamer et al, 2011) and indirectly (Godschalx et al, 2015). The latter is illustrated by a study with potted plants placed in the field that reported positive effects of the addition of Rhizobium sp.…”
Section: The Effect Of Nitrogen-fixing Rhizobia On Aboveground Herbivmentioning
confidence: 99%
“…However, such studies of two-way interactions (e.g. between a plant and its herbivore or an insect herbivore and its symbionts) cannot always predict the responses of organisms in a community [7][8][9]. Here, we adopt a community approach and simultaneously examine the role of both plant -and insect -microbial interactions in modulating the plant -herbivore interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Belowground colonization of roots by Rhizobium has been found to interact with aphids and other aboveground herbivores (Kempel et al, 2009;Katayama et al, 2010Katayama et al, , 2011Martinuz et al, 2012). For example, root colonization by Rhizobium has been found to promote plant resistance to insect pests (Thamer et al, 2011). However, Rhizobium colonization of roots has also been related to an increase in aphid and fungal incidences on leguminous shoots, which has been attributed to improved nutritive suitability of the host plant due to nitrogen fixation (Dean et al, 2009(Dean et al, , 2014Naluyange et al, 2014).…”
Section: Introductionmentioning
confidence: 99%